Penyusunan Strategi Operasional Usahatani Jagung Berbasis Evaluasi Manajerial Faktor Produksi untuk Meningkatkan Efisiensi dan Kualitas Hasil Panen - Intan Pijar Azzahra; Veralianta Br Sebayang (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The low proportion of Grade A harvest quality in Hokkaido corn farming remains a challenge for horticultural agribusiness practitioners. This study aims to develop an operational strategy based on a managerial evaluation of key production factors to improve technical efficiency and harvest quality. The research was conducted at PT Agricole Indonesia Makmur, Cianjur, using data from 24 planting periods in 2024. Six production input variables were analyzed to identify the most influential factors on yield quantity and quality. The results show that only three variables watering frequency, organic fertilizer, and plant age at harvest consistently contributed significantly to the production of Grade A output. Although these variables are inelastic, they play a critical role in maintaining quality. The proposed strategy includes a 10% increase in harvest quantity and a 30% conversion from Grade B to Grade A. Simulation results indicate an additional 7.67 kg of Grade A yield per planting period, generating a value increase of IDR 239,490. The strategy is considered feasible with a positive Return on Investment (ROI) of 14.04% assuming a Grade A selling price of IDR 35,000/kg.